Developing personas to examine older adult engagement with televised direct-to-consumer advertisements: A theory based approach - Emily L. Hoffins, MS; Taylor L. Watterson, PharmD, PhD; Michelle A. Chui, PharmD, PhD (Exploratory Research in Clinical and Social Pharmacy)
Background: The average adult in the United States views up to 16 h of direct-to-consumer television advertisements (DTCA) per year, far exceeding time they spend with their primary care team. DTCAs present a unique opportunity to extend medical education beyond traditional medical settings and into the daily lives of patients. This is particularly valuable for populations with changing healthcare needs, such as older adults. As pharmaceutical companies invest in DTCAs, there is a growing need to identify what characteristics make viewers more likely to retain and act on medication information presented in DTCAs. Objective: This paper presents a theory based approach to developing personas of older adult DTCA viewers that categorize characteristics influencing their approach to healthcare engagement. Methods: In 2023, 25 older adult participants watched a one minute DTCA followed by a semi-structured interview. The interview guide applied concepts from the human factors engineering Communication-Human Information Processing model (C-HIP). C-HIP provided structure for both identifying personal characteristics that influence cognition and examining how these factors influence older adult's ability and desire to retain information from DTCAs. Personas were iteratively developed using qualitative analysis. Results: The study yielded three main older adult DTCA viewing personas. These include: 1) medication averse older adults who actively avoid taking medications, 2) information seeking older adults who independently research health information to participate in shared-decision making, and 3) medication adhering older adults who prefer their provider to control decisions. Conclusion: Constructing older adult personas provides insights into the heterogeneity among older adult approaches to engaging with health information. Each persona represents unique information priorities and personal characteristics of older adults when viewing advertisements, thus presenting a need for tailored patient-centered messaging in commercials.